2003
DOI: 10.1046/j.1445-2197.2003.t01-1-02613.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of glyceryl trinitrate‐verapamil with other dilators of human saphenous vein

Abstract: The present paper demonstrates the following conclusions: (i) glyceryl trinitrate is a rapidly acting dilator of the human isolated SV. (ii) GTN-V combination is a potent combination causing a maximum dilator effect that is significantly greater than single agents including SNP and N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…However, efforts to mitigate the effect of the learning curve would become an important public health issue if the results of our pilot study are ultimately confirmed. Prior studies have suggested that as few as 20 cases of experience are required to complete the learning curve of EVH [16]. In contrast, we found that learning was not complete with even close to 100 cases of experience when using conduit injury on OCT imaging as a more a sensitive metric for learning.…”
Section: Commentcontrasting
confidence: 62%
See 2 more Smart Citations
“…However, efforts to mitigate the effect of the learning curve would become an important public health issue if the results of our pilot study are ultimately confirmed. Prior studies have suggested that as few as 20 cases of experience are required to complete the learning curve of EVH [16]. In contrast, we found that learning was not complete with even close to 100 cases of experience when using conduit injury on OCT imaging as a more a sensitive metric for learning.…”
Section: Commentcontrasting
confidence: 62%
“…Division of branches was performed with bipolar electrocautery set at 20 W. Proximal saphenous vein ligation was performed through a separate stab incision. After removal from the leg, the saphenous vein was flushed and stored in a Plasma-Lyte solution (Baxter International, Inc, Deerfield, IL) containing heparin, glyceryl trinitrate, and verapamil [16]. After grafting, blood flow was measured in each SVG using transit time ultrasound (Medistim, Inc, Oslo, Norway).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicorandil relaxed the contraction of the HIMA, HSV, and radial artery induced by phenylephrine, KCl, and the TxA 2 analogue U46619. 18,[20][21][22] In the present study, phenylephrine, an a 1 -adrenoceptor agonist, was used to contract the HSV and HIMA. Phenylephrine is a potent vasoconstrictor that can contract arterial and vein grafts even when endothelium is intact.…”
Section: Discussionmentioning
confidence: 99%
“…Procured SVGs and RA grafts were initially flushed with heparinized saline by using syringe injection, with no methods used to control the distending pressure (54%), to prepare the conduits for grafting. The remainder of the conduits were flushed in a plasmalyte solution containing glyceryl trinitrate and verapamil 11 using controlled distending pressure at less than 100 mm Hg. The proximal aortic anastomoses were performed first for each SVG or RA graft with a partial occluding aortic clamp.…”
Section: Surgical Techniquementioning
confidence: 99%